Use of Automated External Defibrillators in US Federal Buildings: Implementation of the Federal Occupational Health Public Access Defibrillation Program - Kilaru, Austin S. (2014)
OBJECTIVE: Federal Occupational Health (FOH) administers a nationwide public access defibrillation program in US federal buildings. We describe the use of automated external defibrillators (AEDs) in federal buildings and evaluate survival after cardiac arrest. METHODS: Using the FOH database, we examined reported events in which an AED was brought to a medical emergency in federal buildings over a 14-year period, from 1999 to 2012. RESULTS: There were 132 events involving an AED, 96 (73%) of which were due to cardiac arrest of cardiac etiology. Of 54 people who were witnessed to experience a cardiac arrest and presented with ventricular fibrillation or ventricular tachycardia, 21 (39%) survived to hospital discharge. CONCLUSIONS: Public access defibrillation, along with protocols to install, maintain, and deploy AEDs and train first responders, benefits survival after cardiac arrest in the workplace.